A Novel Scoring System for Rupture Risk Stratification of Intracranial Aneurysms: A Hemodynamic and Morphological Study - Jiang, Pengjun; Liu, Qingyuan; Wu, Jun; Chen, Xin; Li, Maogui; Li, Zhengsong; Yang, Shuzhe; Guo, Rui; Gao, Bin; Cao, Yong; Wang, Shuo (Frontiers in Neuroscience, 2018)
Objective: The aim of the present study is to investigate the potential morphological and hemodynamic risk factors related to intracranial aneurysms (IAs) rupture and establish a system to stratify the risk of IAs rupture to help the clinical decision-making. Methods: Patients admitted for single-IAs were selected from January 2012 and January 2018. A propensity score matching was conducted to match patients. The morphological parameters were obtained from high solution CTA images, and the hemodynamic parameters were obtained in accordance with the outcomes of computational fluid dynamics (CFDs) simulation. Differences in the morphologic and hemodynamic parameters were compared. The significant parameters were selected to establish a novel scoring system (Intracranial Aneurysm Rupture Score, IARS). The comparison was drawn between the discriminating accuracy of IARS and the Rupture Resemblance Score (RRS) system to verify the value of IARS. Then, a group of patients with unruptured IAs was stratified by IARS and RRS system separately and was followed up to verify the value of IARS. The outcome of different stratifications was compared. Results: The matching process yielded 167 patients in each group. Differences of statistical significance were found in length (p=0.001), perpendicular height (H) (p<0.001), aspect ratio (AR) (p<0.001), size ratio (SR) (p<0.001), deviated angle (DA) (p<0.001), normalized average wall shear stress (NWSSa) (p<0.001), wall shear stress gradient (WSSG) (p<0.001), low shear area ratio (LSAR) (p=0.01) and oscillatory shear index (OSI) (p=0.01). Logistic regression analysis demonstrated SR, DA, NWSSa, LSAR and OSI as the independent risk factors of IAs rupture. SR, DA, LSAR and OSI were finally selected to establish the IARS. Our present IARS showed a higher discriminating value (AUC 0.81 vs 0.77)in comparison with the RRS (SR, NWSSa and OSI) . After follow-up, seven patients were subject to IAs rupture. 5/26 in high-risk group stratified by IARS, yet 7/57 in high-risk group stratified by RRS. The accuracy of IARS was further verified (19.2% vs 12.3%, AUC: 0.723 vs 0.673, respectively). Conclusions: SR, DA, NWSSa, LSAR and OSI were considered the independent risk factors of IAs rupture. Our novel IARS showed higher accuracy in discriminating intracranial aneurysm rupture in comparison with RRS.